Structural and Photocatalytic Properties of TiO2/Zeolite Synthesized using Sol-Gel Method - Nur Aini; Fahmi Eksa Sagita; Khoridatud Diyanah; Aminatus Arifah; Siti Nur Chasanah; Anton Prasetyo (ALCHEMY, 2019)
Titanium dioxide (TiO2) is supported into natural zeolite to enhance its photocatalytic activity. TiO2/zeolite is synthesized using sol-gel method at composition ratio of 5:95; 10:90; 20:80 and 30:70%. Structural properties are measured by X-ray diffraction showed TiO2/zeolite in various composition has characteristic of anatase and modernite phase. The energy dispersive spectroscopy characterization shows TiO2/zeolite containing Ti element which indicates that TiO2is successfully supported into natural zeolite. Vibration mode of Infrared and Raman spectra tend shifted to higher wavenumber as increasing of TiO2 content indicating the higher energy vibration due to molecular interaction between TiO2 and zeolite. Photocatalytic activity test toward methylene blue degradation shows that TiO2/zeolite has higher activity than TiO2 and zeolite itself.Keywords: Photocatalyst, titanium dioxide, zeolite